Congenital eruptive vellus hair cysts. - Seok, J.; Ko, E.J.; Park, K.Y. (European Journal of Pediatric Dermatology, 2015)
Eruptive vellus hair cysts (EVHC) represent a developmental abnormality of vellus hair follicle. They are usually localized on the chest and proximal extremities, but they may be present at unusual sites, including the face, groin and buttocks. The average age at onset is 16.7 years, and in nearly 85% patients EVHC occur by the age of 25 years. We report here an unusual case of congenital eruptive vellus hair cyst localized on the forehead in a 7-yearold girl.